Model Pendampingan Transformasi Digital Terintegrasi Dalam Meningkatkan Kemandirian Dan Daya Saing UMKM Kota Cirebon - Bani Nurhakim; Willy Prihartono; Putri Indah Lestari; Revan Faturochman (CV. Multi Kreasi Media, 2025)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs) as they navigate shifting consumer behaviors, intensifying competition, and the evolution of technology-driven trade ecosystems. However, many MSMEs still face various obstacles, including limited digital literacy, suboptimal use of social media and online marketplaces, weak brand identity, disorganized administration and financial record-keeping, and a lack of integration between marketing, transaction, and customer management processes. This community service initiative aims to implement an integrated digital transformation mentoring model to enhance the self-reliance and competitiveness of MSMEs in Cirebon City. The implementation employs a participatory and needs-based mentoring approach, comprising stages such as needs identification, digital maturity mapping, training, technology implementation, intensive mentoring, monitoring, and evaluation. The mentoring program focuses on five key dimensions: digital branding, digital marketing, digital commerce, digital payments, and digital business management. Results indicate that this phased and integrated mentoring approach successfully improved participants' understanding of digital transformation, their ability to manage business social media, the quality of promotional content, the utilization of digital sales channels and payment methods, and their awareness regarding the importance of business data recording. This model underscores that MSME digital transformation cannot be achieved solely through one-way training; rather, it requires a continuous process involving assessment, hands-on practice, mentoring, evaluation, and follow-up. The program is expected to serve as a replicable and scalable MSME empowerment model, fostered through collaboration among higher education institutions, local government, business communities, and other stakeholders.